Matrix structures in management of quality of educational and scientific work of Ukrainian universities - Velychko, Oleksandr; Величко, Олександр Петрович; Velychko, Liudmyla; Величко, Людмила Анатоліївна (Business Perspectives, 2018)
For the past few years, major progress in providing academic autonomy to Ukrainian universities has been made. However, a large number of universities even now remain the establishments with post-Soviet bureaucratic type of organization of management. For the past few years, major progress in providing academic autonomy to Ukrainian universities has been made. However, a large number of universities even now remain the establishments with post-Soviet bureaucratic type of organization of management.
Матричні структури в управлінні якістю освітньої та наукової діяльності українських університетів
For the past few years, major progress in providing academic autonomy to Ukrainian universities has been made. However, a large number of universities even now remain the establishments with post-Soviet bureaucratic type of organization of management. As a result, a severe and complicated system of control over current activity has been supported, which requires from scientific and pedagogical workers not only to work effectively, but also to keep the set of rules and procedures. The purpose of the research is to search for possibilities of efficient application by modern universities of flexible matrix structures of management while forming their own internal system of quality control. Threats from bureaucratic management have been generalized for competitiveness of a modern university at the market of educational, scientific and consulting services. The concept and methodology on de-bureaucratization of the system of quality in higher education on the basis of the process approach of the theory of management and rationalistic logistics obtained further development. The mechanism of management of quality at the operational level of the university through integration of the segment-focused approach, system of grading and matrix organization of regular processes has been improved. Ways to apply matrix structure the middle and low levels of managing university have been suggested. Author’s recommendations have been provided towards rating evaluation of work of departments and their segment-focused structural organization. The matrix structure of management of quality of carrying out the temporary research project in the university under the conditions of the budget commission has been developed and practically tested. Протягом останніх років відбувся значний прогрес у наданні українським вишам статусу академічної автономії. Однак значна частина університетів і дотепер залишаються установами з пострадянським бюрократичним типом організації управління. Унаслідок підтримується громіздка і складна система контролю над поточною діяльністю, яка вимагає від науково-педагогічних працівників не стільки ефективної праці, скільки дотримання набору правил і процедур. Метою дослідження є пошук можливостей ефективного використання сучасними університетами гнучких матричних структур управління при формуванні власних внутрішніх систем забезпечення якості. Узагальнено загрози від бюрократизації управління для конкурентоспроможності сучасного закладу вищої освіти на ринку освітніх, наукових та консультаційних послуг. Знайшла подальший розвиток концепція та методологія дебюрократизації системи якості вищої освіти на засадах процесного підходу теорії менеджменту та раціоналістичної логістики. Удосконалено механізм менеджменту якості на операційному рівні університету через інтегрування сегментоорієнтованого підходу, системи грейдингу та матричної організації регулювання процесів. Запропоновано шляхи використання матричних структур на середньому та низовому рівнях управління університетом. Наведено авторські рекомендації щодо рейтингового оцінювання роботи кафедр та їх сегментоорієнтованої структурної організації. Розроблено та перевірено в практичних умовах модель матричної структури управління якістю виконання тимчасового дослідницького проекту університету в умовах державного замовлення.
Keywords: higher education; вища освіта; bureaucracy; структури управління; structures of management; структури управління; flexibility; гнучкість; quality system; система якості